Multidimensional advances in neural interface technology for peripheral nerve repair: From material innovation to clinical translation - Jianchao Wu; Qixin Han; Dingkun Gui; Yun Qian (Materials Today Bio)
This review evaluates the research progress and clinical application potential of neural interface technology for peripheral nerve injury (PNI). Due to the limited endogenous regenerative capacity of the peripheral nervous system after injury, the impaired function of the innervated area seriously affects the life quality of patients. Neural interfaces offer a transformative strategy for functional reconstruction by establishing bidirectional communication pathways between the nervous system and external devices. Through a critical analysis of high-impact literature, this article develops a comprehensive review framework encompassing four key dimensions: advancements in material science, technological innovation pathways, clinical translation validation, and existing challenges. Current evidence demonstrates that neural interface materials evolved from traditional rigid substrates to flexible conductive polymers, multifunctional nanocomposites, biodegradable bioactive scaffolds, and environmentally responsive smart materials. Technological breakthroughs include tissue-compliant flexible micro-nano fabrication, wireless self-powered systems, closed-loop neural feedback control, and multimodal precision modulation. Preclinical and clinical researches validated the therapeutic efficacy of neural interfaces in promoting axon regeneration, managing chronic pain, and restoring sensorimotor function. However, persistent challenges (such as limited long-term interfacial stability, post-implantation inflammatory responses, signal quality attenuation, and interindividual therapeutic heterogeneity) hinder widespread clinical adoption. Future research should prioritize interdisciplinary integration to develop: physiologically adaptive material interfaces, intelligent closed-loop modulation systems, personalized treatment strategies with predictive modeling, and mechanistic insights into neuro-electronic interface interactions. These advances will enable neural interface technologies to achieve biosafety, functional durability, and therapeutic precision for revolutionary treatment paradigms.